Prognozowanie w przedsiębiorstwie - kluczowe zagadnienia - Dittmann, Paweł (Forecasting in Companies - Essential Problems, 2006)
The paper shows the essential problems of forecasting in companies. It identifies the main forecasting steps: determining of the forecasting assumptions, preliminary analysis of the forecasting data, the choosing of forecasting methods and evaluation the quality of forecasts. There has been also described the problem of the integration of forecasting methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 13-18